Teachers’ Perception of Tongue Twisters in Teaching Phonology and Listening - Sholihatul Hamidah Daulay; Lainatusshifa Saragih; Wildan As’at Taufik Hasibuan (EXCELLENCE: Journal of English and English Education, 2025)
This study investigated teachers’ perception of using tongue twisters in teaching phonology and listening in an EFL context. Using a qualitative descriptive design, data were collected through a semi-structured interview with an English teacher who had experience implementing tongue twisters in pronunciation and listening classes. The findings reveal that the teacher perceives tongue twisters as an effective tool for enhancing phonological awareness, improving articulation, and increasing students’ sensitivity to phonemic contrasts. The teacher also believes that tongue twisters support listening development by strengthening learners’ ability to discriminate minimal pairs, recognize stress and rhythm patterns, and attend to detailed sound differences. Despite these benefits, several challenges were identified, including students’ shyness, difficulties in selecting level-appropriate tongue twisters, limited class time, and learners’ tendency to prioritize speed over accuracy. Overall, the results indicate that tongue twisters serve as a motivating and practical strategy that links pronunciation and listening practice, although their success depends on careful planning and pedagogical adaptation. The study highlights the need for teacher training in pronunciation pedagogy and suggests integrating tongue twisters with other phonological and listening activities to optimize learning outcomes.